Roots and Nodules Response Differently to P Starvation in the Mediterranean-Type Legume Virgilia divaricata - Stevens, Gary G.; Pérez-Fernández, María A.; Morcillo, Rafael J. L.; Kleinert, Aleysia; Hills, Paul; Brand, D. Jacobus; Steenkamp, Emma T.; Valentine, Alex J. (Frontiers in Plant Science, 2019)
Virgilia divaricata is a tree legume that grows in the Cape Floristic Region (CFR) in poor soils. A comparison between high and low phosphate growth conditions between roots and nodules was conducted and evaluated for the plants ability to handle low phosphate (LP) stress conditions in Virgilia divaricata. We showed that the plant copes with low phosphate stress through an increased allocation of resources, reliance on biological nitrogen fixation (BNF) and enhanced enzyme activity, especially phosphoenolpyruvate carboxylase . Nodules had a lower percentage decline in P compared to roots to uphold their metabolic functions. These strategies partly explain how V. divaricata can sustain growth despite LP conditions. Although the number of nodules declined with LP (i.e., 34% compared to the 88% decline in roots), their biomass remained unchanged in spite of an overall decline in plant dry weight. We attribute this behaviour to P conservation strategies in LP nodules that imply an increase in a metabolic bypass that operates at the phosphoenolpyruvate branchpoint in glycolysis. The enhanced activities of nodule phosphoenolpyruvate carboxylase, malate dehydrogenase and malic enzime, whilst pyruvate kinase declines, suggests that under LP conditions an adenylate bypass was in operation either to synthesize more organic acids or to mediate pyruvate via a non-adenylate requiring metabolic route. Both possibilities represent a P-stress adaptation route and this is the first report of its kind for legume trees that are indigenous to low P, acid soils. Although BNF declined by a small percentage during LP, this P conservation was evident in the unchanged BNF efficiency per weight, and the increase in BNF efficiency per mol of P. It appears that legumes that are indigenous to acid soils, may be able to continue their reliance on BNF via increased allocation to nodules and also due to increase their efficiency for BNF on a P basis, owing to P-saving mechanisms such as the organic acid routes.